IMPLEMENTASI EVALUASI NILAI-NILAI PENDIDIKAN ISLAM PADA SANTRI DI MADIN NURUL QODIM AL-MANSHURIYAH DESA TAMAN SARI-WONOREJO-PASURUAN - Fauzi; Asrul Anan (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Education is a system that must be run collectively with other existing systems in order to achieve the goals set to improve the quality of human life in all aspects of life. Evaluation in the teaching and learning process is a very important component and cannot be separated from the whole learning process. The problems of Islamic education require a vision and orientation of education that integrates the dimensions of cogintif, affective and psychomotor as well as good moral education. The problems experienced at this time are students in the learning process to get a cleric and ustadzah assessment from the aspect of knowledge alone do not consider other aspects, students are static and become a subject in the learning process, lack of creativity of students in the class in receiving and applying learning materials provided by cleric and cleric. In education there is a theory that is familiar in education circles, namely Bloom's taxonomic theory developed by Bloom and Krathwohl with this theory, Ustadz and Ustadzah can lead to students using three aspects, namely cognitive, affective, and psychomotor aspects in evaluating the values ​​of Islamic education.